ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNTUNGAN PEDAGANG SOUVENIR DI KECAMATAN UBUD, KABUPATEN GIANYAR, BALI - Rahsyani, Anak Agung Karin; Putu Widanta, Anak Agung Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
The profits obtained by souvenir traders in Ubud District, Gianyar are determined by several factors, some of which are working capital, working hours, product quality, and sales volume. This study aims to analyze the effect of working capital, working hours and product quality on profits with sales volume as an intervening variable for souvenir traders in Ubud District, Gianyar. In this study using primary and secondary data through direct interviews to 89 respondents with the sampling method Proportional Stratified Random Sampling. The data analysis technique is in the form of descriptive analysis technique and path analysis. The results showed that working capital, working hours, product quality, and sales volume had a positive effect on the profits of souvenir traders in Ubud District, Gianyar. The suggestion that can be given in this research is to increase the profit of souvenir traders in Ubud District, Gianyar, it is better to optimize working capital, working hours, product quality and sales volume so that the profits obtained are greater.